Integrated Teaching of MBBS Curriculum 2021 in Bangladesh: Challenges, Pitfalls and Solutions (Bangladesh Journal of Medical Education, 2026)
Background: In medical education correlation of theoretical and practical knowledge is most important aspect of learning. Hence the teaching should also be done in integrated manner, where different subjects unify to teach a relevant topic in more effective manner. Objective: This study aimed to identify the major issues influencing the implementation of integrated teaching in MBBS curriculum 2021 and to suggest recommendations to solve these. Methods: A cross-sectional study was conducted among 337 MBBS students (2021 curriculum) and 176 faculty members from government and non-government medical colleges in Bangladesh. Institutes were selected through stratified sampling, and participants through random sampling. Data were collected via pretested questionnaires and in-depth interviews. Feedback on integrated teaching was analyzed using frequency, percentage, and appropriate statistical tests, while thematic analysis was applied to interview findings. Results: Students strongly supported the need for training of the educational workforce (mean 4.11±0.77), while their views on integrated teaching for OSPE were neutral (mean 2.99±1.12). Non-government respondents generally provided higher ratings, with significant group differences in areas such as teaching hours, student-teacher ratio, adequacy of workforce, resources, and training needs (p